The Teachers’ Perceptions of the Implementation of the Merdeka Curriculum at Public Elementary School 07 Enam Lingkung - Silvi Khairi; Gusnita Efrina; Gingga Prananda; Rica Azwar (The Future of Education Journal, 2025)
This study was motivated by the need to understand teachers’ perceptions of the implementation of the Merdeka Curriculum as well as the obstacles encountered in its application at SD Negeri 07 Enam Lingkung. The purpose of this research is to examine teachers’ perceptions of the implementation of the Merdeka Curriculum and to identify the challenges faced by teachers in its implementation. This study employs a qualitative research approach with a descriptive method. Data were collected through interviews, observations, and documentation involving the principal and teachers. The results of this research show that most teachers have a positive perception of the Merdeka Curriculum implementation, including the fact that the learning process is not significantly different from the previous curriculum, the simplification of learning tools, the flexibility of teaching modules that support differentiated learning, and the use of teaching modules as the main instructional resource. However, teachers also face several challenges, such as limited experience in applying the principles of Merdeka Belajar, insufficient basic teaching competencies, limited understanding of the Merdeka Curriculum concept, lack of creativity and innovation in teaching, limited use of media and learning models, suboptimal adaptation to curriculum changes, and insufficient professional support and mentoring. The conclusion of this study is that although the implementation of the Merdeka Curriculum at SD Negeri 07 Enam Lingkung has been running fairly well, further training and mentoring are necessary to enable teachers to implement the curriculum optimally.